Is Gold A Good Hedge Against Inflation? Empirical Evidence in Malaysia - Mohd Fahmi Ghazali,; Hooi Hooi Lean,; Zakaria Bahari, (Kajian Malaysia, 2015)
This paper studies the role of gold quoted in domestic currency as an inflation hedge in Malaysia from July 2001 to November 2011. Using the Malaysian monthly domestic gold and consumer price index (CPI), we examine the relationship between gold return and inflation in Malaysia via correlation coefficients and linear regression model. This paper finds no significant relationship between gold return and inflation, gold return and expected inflation and gold return with unexpected inflation, which led to the conclusion that domestic gold is not a good hedge against inflation in Malaysia. It is also not an excellent store of value over a relatively short period of time as it is unable to retain its sustainable purchasing power.